Art, Identity, and Justice: The Role of Art in Shaping the Representation of Ethnic Minorities in Indonesia (Indonesian Art and Justice Review, 2025)
Ethnic minorities in Indonesia, such as Chinese-Indonesians, indigenous groups, and other marginalized communities, have long struggled for representation and recognition within the national cultural narrative. This paper investigates the role of art in asserting the identity of these groups and in challenging the stereotypes and stigmas often associated with them. By examining the work of Indonesian artists from ethnic minorities, this study highlights how art becomes a vehicle for cultural justice, allowing these communities to reclaim and reframe their stories, histories, and representations in the public sphere. The paper explores how art challenges hegemonic cultural norms and provides a space for cultural expression, identity formation, and resistance, emphasizing the transformative power of art in promoting ethnic justice.